Reading the Vampire. - Gelder, Ken (Routledge, 1994)
Gelder examines the vampire in its various film and narrative manifestations, placing the vampires in their cultural contexts. The author draws upon films such as Murnau's Nosferatu and books such as Anne Rice's vampire chronicles.